Folder data storage authentication using graphical password / Muhamad Haziq Mohd Rosdi - Mohd Rosdi, Muhamad Haziq (2021)
In the modem era of technology, we are demanded to make sure our privacy secure especially while keep our data from illegal authorized. Nowadays our data is not secure since there are many ways and methods to crack out security system. Even we were providing with the highest security system but still our security will be attacking just the matter of time how long it will take to crash our security. This project was proposed to solve that problem which is by create the best authentication for the folder storage to increase it security level. From the research, people mostly use alphanumerical as a password to lock their folder or data from another trespassing, so I assume that alphanumerical is easier to crack or being attack by the hackers. So, with graphical password authentication, it might be different because according to the research, graphical image is hard to crack. I found that graphical password is easier to remember rather than alphanumerical password. Plus, graphical image authentication is new in our research and it was rarely used for security system, hi conclusion, this project will develop a system of folder data storage authentication using graphical password by using various way and method to accomplish this project objectives.